Digital Entrepreneurship as a Driver of Innovation Ecosystems in Developing Countries - Wenaldo Abdi Gunawan; Nila Sari; Andrian Syahputra; Ismail Zikri; Arthur Freeman (ADI Bisnis Digital Interdisiplin Jurnal, 2026)
This abstract is developed with a background that rapid digital technological advancement has positioned digital entrepreneurship as a critical driving force in shaping and accelerating innovation ecosystems, particularly in developing countries that face structural limitations such as restricted access to resources, markets, and conventional infrastructure. Digitalization enables entrepreneurs to leverage digital platforms to create value, foster collaboration, and stimulate inclusive and sustainable innovation. Based on this background, the Object of this study is to analyze the role of digital entrepreneurship as a key catalyst in driving innovation ecosystems in developing countries, as well as to identify the mechanisms of interaction among ecosystem actors mediated by digital technologies. The Method employed in this research adopts a qualitative approach through a systematic literature review of reputable international journal articles published within the last five years, complemented by conceptual analysis to construct an integrated analytical framework. The Result of the study indicates that digital entrepreneurship significantly strengthens innovation ecosystems by enhancing cross-sector collaboration, accelerating knowledge diffusion, improving business process efficiency, and expanding access to markets and financing opportunities. Furthermore, digital platforms are shown to play a vital role in bridging structural gaps commonly found in developing economies. The Conclusion of this research highlights that digital entrepreneurship should not be viewed merely as technology-based economic activity, but rather as a strategic catalyst for building adaptive, inclusive, and sustainable innovation ecosystems, thereby requiring integrated policy support and coordinated development strategies at both national and regional levels.